1999
DOI: 10.1149/1.1391871
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Passivation of InP/InGaAs Metal‐Semiconductor‐Metal Photodetectors

Abstract: The InGaAs finger-interdigitated metal-semiconductor-metal photodetector (MSM-PD) is potentially the most promising candidate for ultrafast photodetectors for the wavelength range 1.3-1.55 m and long-haul optical fiber communication systems and interconnects. It has many advantages over p-i-n structures, such as low parasitic capacitance, wide bandwidth, planar structure, and simple fabrication, as well as compatibility with field-effect transistors (FETs).An MSM-PD consists essentially of two back-to-back Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It was reported that sulfur treatment is very effective in reducing the surface states and surface recombination velocity in III-V compound semiconductors. [7][8][9][10][11][12] Of the various sulfur treatments, only the ͑NH 4 ͒ 2 S x treatment achieved promising results due to its capacity to etch the native oxide and the GaAs surface and to tie up the dangling bonds with sulfur on a freshly exposed prismatic GaAs surface. Although increasing immersion time promotes the performance, longer immersion time causes a higher surface roughness and a decline in the mobility of electrons by high sulfide contamination and chemical reaction.…”
mentioning
confidence: 99%
“…It was reported that sulfur treatment is very effective in reducing the surface states and surface recombination velocity in III-V compound semiconductors. [7][8][9][10][11][12] Of the various sulfur treatments, only the ͑NH 4 ͒ 2 S x treatment achieved promising results due to its capacity to etch the native oxide and the GaAs surface and to tie up the dangling bonds with sulfur on a freshly exposed prismatic GaAs surface. Although increasing immersion time promotes the performance, longer immersion time causes a higher surface roughness and a decline in the mobility of electrons by high sulfide contamination and chemical reaction.…”
mentioning
confidence: 99%
“…Generally, photodetectors with a lower dark current are more sensitive to the weak light. Adjusting the electrode materials, [ 37,204–206 ] using asymmetric electrodes, [ 207–211 ] introducing a barrier enhancement layer, [ 212–215 ] surface passivation, [ 216–218 ] atom implantation, [ 219,220 ] and atom doping [ 221,222 ] can effectively reduce the dark current of MSM‐PDs.…”
Section: Improving the Performances Of Msm‐pdsmentioning
confidence: 99%
“…introduced a high‐performance surface passivated InGaAs MSM‐PD with an InP barrier enhancement layer. [ 216 ] They found that by treating the InP surface with sulfur, stable and repeatable device performances were achieved. The device had an extremely low capacitance of 200 fF, a dark current of 200 nA at 10 V bias, and a breakdown voltage of about 20 V. The corresponding responsivity was up to 0.75 A W −1 , and the cutoff frequency was 20 GHz.…”
Section: Improving the Performances Of Msm‐pdsmentioning
confidence: 99%
“…Devices with different metal electrodes show lower leakage current; however this method needs one more mask and adds to the fabrication processing. Antireflection coating [15] and surface passivation, are other approaches to dark current reduction that help to passivate the surface, and reduce the surface states using materials like oxide [16], SiC>2 [17], sulphur passivation [18], and polyimide passivation [19]. Including a Schottky barrier enhancement layer in between the metal and active layer is another approach for reducing the dark current of MSM photodetectors by increasing the Schottky barrier height of the metal semiconductor junction.…”
Section: Review On Photodetectorsmentioning
confidence: 99%
“…18 shows the photocurrent versus hydrogen concentration of the samples. Photocurrent at different hydrogen concentrations…”
mentioning
confidence: 99%